The Effects of Planning and Handwriting Style on Quantity Measures in Secondary School Children’s Writing - Williams, Gareth J.; Larkin, Rebecca F.; Coyne-Umfreville, Emily; Herbert, Toni C. (Frontiers in Psychology, 2019)
The study aimed to evaluate the proposer, translator, editor and transcriber process model of writing in the context of secondary school children. Eighty-three children completed written texts under conditions that facilitated the proposer and placed resource demands on the transcriber. It was found that the number of words, lexical richness, and the number of sentences were affected by transcription resource demands while the number of sentences was increased when the proposer was facilitated. There were also by-gender interactions that indicated male writers and female writers completed the tasks to different product levels. The discussion proposes that future developments of the model take into account a more direct interaction between the transcriber and translation level processes when considering this age group.